Dysexecutive Syndrome: A Specific Pattern of Cognitive Impairment in Systemic Sclerosis - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2012)
Background and Purpose: Systemic sclerosis (SSc) is a connective-tissue disorder characterized by microvascular damage and tissue fibrosis. Although overt nervous system involvement is unusual in SSc, imaging studies have shown cerebral hypoperfusion. We evaluated cognitive functions in patients with SSc who had no history of neurological involvement, to seek cognitive impairment caused by the suggested cerebral hypoperfusion. Methods: We performed a comprehensive neuropsychological test battery on 31 patients with SSc and on 2 groups of age-adjusted, sex-adjusted, and education-adjusted controls: 15 patients with rheumatoid arthritis and 20 healthy volunteers. Results: The patients with SSc scored significantly worse on most of the measures of executive function than the 2 control groups (P < 0.05). However, both patient groups did worse than the healthy controls on measures of attention and memory (P< 0.005). Conclusions: Our results suggest that patients with SSc have a specific pattern of cognitive impairment: the dysexecutive syndrome. Attentional and memory problems, however, may arise from other confounders such as disease duration and chronic medication use. SSc may be a rare cause of vascular cognitive impairment.
Keywords: dysexecutive syndrome; cognition; systemic sclerosis; Raynaud phenomenon; LUPUS-ERYTHEMATOSUS PATIENTS; NEUROPSYCHIATRIC SYNDROMES; NEUROLOGIC MANIFESTATIONS; MEMORY PERFORMANCE; DISEASE-ACTIVITY; SCLERODERMA; PREVALENCE